GENDER ASPECTS OF ENGLISH PHRASEOLOGY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In the field of world linguistics, determining the expression of national-cultural and gender characteristics is considered one of the important tasks, and this article is devoted to the gender aspect of the research of English phraseology.